Quality Deterioration of Tomatoes Using Three Different Storage Methods - Bankole, Yakubu; Abanigbe, Samuel (Mediterranean Journal of Social Sciences, 2012)
Study was conducted at the Microbiology laboratory of Lagos State Polytechnic, Ikorodu to determinequality deterioration of tomatoes sample using plastic, carton and basket storage method for period of 7and 14 days respectively. 1000g matured tomatoes sample were taken from a farm settlement atOdogunyan-Ikorodu, Lagos to determine the physiochemical properties; moisture content (MC), protein (P),fat (FT), fibre (FB), ash (A) and vitamin ‘C’ (VC) of the produce before and after storage, also, microbialcount and pathogenic presence after 24 and 48 hours of storage. Result obtained showed 95.00%MC,2.21%P, 0.30%FT, 0.81%FB, 2.34%A and 67.50mgVC before storage. Tomatoes stored in the carton had thehighest nutritional values in terms of quality; 55.48%MC, 0.85%P, 0.18%FT, 0.58%FB, 1.00%A and2.50mgVC after 14 days. Penicillium, green fungi which grows in ripening fruit was found in the plasticafter 48 hours with about 2.89 * 106 colony count while, sample stored in the carton were more susceptibleto less colony count (1.52 * 106) of fungi after 48 hours. The carton gave better results when compared tobasket and plastic methods of storage in the study area as far as these quality attributes assessed areconcerned.